Parallel versus serial processing dependencies in the perisylvian speech network: A Granger analysis of intracranial EEG data - Gow, David W. (2009)
In this work, we apply Granger causality analysis to high spatiotemporal resolution intracranial EEG (iEEG) data to examine how different components of the left perisylvian language network interact during spoken language perception. The specific focus is on the characterization of serial versus parallel processing dependencies in the dominant hemisphere dorsal and ventral speech processing streams. Analysis of iEEG data from a large, 64-electrode grid implanted over the left perisylvian region in a single right-handed patient showed a consistent pattern of direct posterior superior temporal gyrus influence over sites distributed over the entire ventral pathway for words, nonwords, and phonetically ambiguous items that could be interpreted either as words or nonwords. For the phonetically ambiguous items, this pattern was overlayed by additional dependencies involving the inferior frontal gyrus, which influenced activation measured at electrodes located in both ventral and dorsal stream speech structures. Implications of these results for understanding the functional architecture of spoken language processing and interpreting the role of the posterior superior temporal gyrus in speech perception are discussed.